“A Breath of Fresh Air Worth Spreading”: Media Coverage of Retailer Abandonment of Tobacco Sales - McDaniel, Patricia A. (American Public Health Association, 2014)
Objectives. Media play an important role in the diffusion of innovations by spreading knowledge of their relative advantages. We examined media coverage of retailers abandoning tobacco sales to explore whether this innovation might be further diffused by media accounts. Methods. We searched online media databases (Lexis Nexis, Proquest, and Access World News) for articles published from 1995 to 2011, coding retrieved items through a collaborative process. We analyzed the volume, type, provenance, prominence, and content of coverage. Results. We found 429 local and national news items. Two retailers who were the first in their category to end tobacco sales received the most coverage and the majority of prominent coverage. News items cited positive potential impacts of the decision more often than negative potential impacts, and frequently referred to tobacco-caused disease, death, or addiction. Letters to the editor and editorials were overwhelmingly supportive. Conclusions. The content of media coverage about retailers ending tobacco sales could facilitate broader diffusion of this policy innovation, contributing to the denormalization of tobacco and moving society closer to ending the tobacco epidemic. Media advocacy could increase and enhance such coverage.